Mandible development under gestational protein restriction: cellular and molecular mechanisms - Calsa, Bruno; Menezes, Luan dos Santos; Neves, José Guilherme; Gontijo, José Antônio Rocha; Santamaria-Jr, Milton [UNESP]; Boer, Patrícia Aline (Springer Nature, 2024)
Insufficient evidence regarding how maternal undernutrition affects craniofacial bone development persists. With its unique focus on the impact of gestational protein restriction on calvaria and mandible osteogenesis, this study aims to fill, at least in part, this gap. Female mice were mated and randomized into NP (normal protein) or LP (low protein) groups. On the 18th gestational day (GD), male embryos were collected and submitted to microtomography (µCT), scanning electron microscopy (SEM), energy-dispersive X-ray spectroscopy (EDS), PCR, and autophagy dynamic analyses. The study shows that the LP offspring exhibited lower body mass than the NP group, with µCT analysis revealing no volumetric differences in fetus’s head. EDS analysis showed lower calcium and higher phosphorus percentages in mandibles and calvaria. SEM assessment evidenced higher hydroxyapatite crystal-like (HC) deposition on the calvaria surface in LP fetus. Conversely, lower HC deposition was observed on the mandible surface, suggesting delayed matrix mineralization in LP fetuses with a higher percentage of collagen fibers in the mandible bone. The autophagy process was reduced in the mesenchyme of LP fetuses. PCR array analysis of 84 genes revealed 27 genes with differential expression in the LP progeny—moreover, increased mRNA levels of Akt1, Mtor, Nfkb, and Smad1 in the LP offspring. In conclusion, the results suggest that gestational protein restriction anticipated bone differentiation in utero, before 18GD, where this process is reduced compared to the control, leading to the reduction in bone area at 15 postnatal day previously observed. These findings provide insights into the molecular and cellular mechanisms of mandible development and suggest potential implications for the Developmental Origins of Health and Disease (DOHaD).
Keywords: Autophagy; DOHaD; Gestational protein restriction; Mandible development; Molecular and cellular pathways